INTERNATIONAL AND NATIONAL LEGAL FOUNDATIONS AND MODERN TRENDS OF THE INSTITUTION OF COMPLIANCE CONTROL IN THE PREVENTION OF CORRUPTION - Nabiyev , Bexruz Nodir o‘g‘li (Innovative Development in Educational Activities, 2024)
Currently, early detection, prevention and combating of corrupt situations, as well as elimination of the causes and conditions that create conditions for them, in particular, prevention of conflict of interests, formation of an intolerant attitude towards corruption are important in the bodies and organizations, their territorial and structural divisions. The introduction of preventive measures against corruption is considered to be of great importance. In particular, as a result of the reforms implemented in preventing and fighting corruption at the international level, preventive measures against corruption are entering not only state bodies and organizations involved in it, but also the private sector. This, of course, shows the relevance of preventive measures against corruption.